Effects of Cinnamomum zeylanicum (Ceylon cinnamon) extract on lipid profile, glucose levels and its safety in adults: A randomized, double-blind, controlled trial - Dimuthu Muthukuda; Chamini Kanatiwela de Silva; Saumiyah Ajanthan; Namal Wijesinghe; Anuradha Dahanayaka; Arunasalam Pathmeswaran (PLoS ONE, 2025)
Background Cinnamon has been studied as a possible way to control blood glucose and serum cholesterol levels. However, there are no well-conducted randomized controlled trials that can accurately measure the lipid and glucose-lowering effects of Cinnamomum zeylanicum (C. zeylanicum) extract. This study primarily aimed to evaluate the effect of a standardized C. zeylanicum extract on serum low-density lipoprotein cholesterol (LDL-C) levels and secondarily on other lipid parameters (high-density lipoprotein cholesterol (HDL-C), total cholesterol and triglycerides), glucose levels, anthropometric measures, blood pressure, and safety outcomes in individuals with an LDL level between 100-190mg/dL. Materials and methods This was a randomized, double-blinded, placebo-controlled clinical trial. Participants were allocated to either C. zeylanicum extract or placebo group (1:1 allocation ratio). They were advised to take two capsules per day (1000 mg/day, a dose based on prior clinical studies suggesting potential efficacy and safety). Reduction in LDL-C at 12 weeks (from the baseline value) was compared between the two groups using ANCOVA. A complete-case analysis was adhered to in analyzing the outcome data. Results The mean age (SD) of the 150 participants was 50.4 (10.52) years, and 66% were females. Among the 127 participants assessed at 12 weeks, those in the C. zeylanicum extract arm had a lower LDL-C value than the placebo arm but the difference was not significant (the baseline adjusted mean difference was 6.05mg/dL; 95% CI: -2.43 to 14.52; p = 0.161). However, participants in the C. zeylanicum extract group showed significantly greater reductions in fasting blood sugar (FBS) levels (the baseline adjusted mean difference was 8.59mg/dL; 95% CI: 0.59 to 16.59; p = 0.036). There was a significant interaction effect between the supplement and participants’ glycemic status, with individuals with type 2 diabetes mellitus (T2DM) who received C. zeylanicum extract experiencing a notable reduction in FBS levels (standardized coefficient: -63, 95% CI: -102 to -25; p = 0.002). Conclusions C. zeylanicum extract did not have significantly reduce LDL-C but demonstrated a significant FBS-lowering effect, particularly in individuals with T2DM, with a favorable safety profile. Trials registration The trial was registered with the Sri Lanka Clinical Trials Registry: SLCTR/2021/011.